Implementasi Manajemen Kesiswaan Berbasis Nilai-Nilai Keislaman dalam Penguatan Karakter Religius Peserta Didik di SMA Islam Hasmi Tahun Ajaran 2025/2026 - Nabila, Kayla; Heriansyah; Indah Wahyu Ningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of the digital era and globalization has eroded Islamic values among students; therefore, student management based on Islamic values is necessary to strengthen religious character. This study aims to describe the implementation of student management grounded in Islamic values at SMA Islam HASMI for the 2025/2026 academic year, analyze its impact on strengthening students’ religious character, identify supporting and inhibiting factors, and formulate development strategies. This research employs a qualitative approach with a case study design conducted at SMA Islam HASMI. The subjects include the principal, vice principal for student affairs, teachers, and female students actively involved in religious activities. Data collection techniques consist of participatory observation, in-depth interviews based on the Spiritual Quotient (SQ) theory by Danah Zohar and Ian Marshall, as well as documentation of policies and activity reports. Data analysis applies source triangulation to ensure validity. The findings indicate that the implementation has been effective through daily habituation programs (Dhuha prayer, dhikr, Qur’anic recitation, short religious sermons), the application of a modest Islamic dress code, class-based mentoring (adaptation, time management, career guidance), personal checklists, and supervision by the student council. These practices align with the dimensions of Spiritual Quotient, including meaning in life, transcendence, empathy, and integrity. The overall success rate of the student affairs program reached 87%.